Designing of welding jig for productivity improvement and cost-savings in thresher's cover assembly: A Case Study on CV Citra Dragon Assembly Plant. (August 2019) - Mulyadi, I H; Putri, N T; Muhammad, F
Abstract: Needs for efficient assembly process has led CV Citra Dragon, a medium-scale manufacturing enterprise of agricultural machinery, to utilize welding jig for assembly one part of thresher component as their high demanding product. That component is thresher's cover that has the potential for productivity improvement hence cost savings. Due to categorize as a specific work-holding device for particular purpose and conditions, design processes of a welding jig has been carried out. This has resulted in the development of a welding jig for assembly of thresher's cover. The design of welding jig has been evaluated from possibility to deflect during its operation, and it was identified that deflection magnitude of welding jig construction was relatively low. Thus, it can infer that this welding jig can resist operational loads. Furthermore, the productivity and cost-effectiveness analysis were also conducted to ensure the welding jig having fulfilled the objective of the proposal. The analysis indicated that the assembly process becomes efficient as a welding jig deployed. It was contributed by shortening of assembly cycle times that increase the production rate. Also, affordable cost savings can also be obvious especially for labor cost salary.